Who benefits from firm-sponsored training? - Benoît Dostie (IZA World of Labor, 2020)
Workers participating in firm-sponsored training receive higher wages as a result. But given that firms pay the majority of costs for training, shouldn't they also benefit? Empirical evidence shows that this is in fact the case. Firm-sponsored training leads to higher productivity levels and increased innovation, both of which benefit the firm. Training can also be complementary to, and enhance, other types of firm investment, particularly in physical capital, such as information and communication technology (ICT), and in organizational capital, such as the implementation of high-performance workplace practices.
Keywords: J3; J24; M5; M53; 330; firm-sponsored training; wages; productivity; innovation; complementarity; human capital